Perancangan Augmented Reality Untuk Pembelajaran Gerakan Senam Aerobik Menggunakan Metode Marker-Based Tracking - Gita Amanda; Siti Sundari (LKP KARYA PRIMA KURSUS, 2025)
The development of Augmented Reality (AR) technology has had a significant impact on the field of education, particularly in delivering learning materials in a more interactive and engaging manner. This study aims to design and develop an Augmented Reality application as a learning tool for aerobic exercise movements using the marker-based tracking method. This method utilizes visual markers to display virtual objects in the form of aerobic movement animations directly through mobile devices. The design process includes needs analysis, system design, application development using Unity and Vuforia SDK, and system functionality testing. The test results show that the application can accurately and responsively display aerobic exercise movements when the marker is detected by the camera. Furthermore, the application is considered helpful for users, especially beginners, in understanding and following aerobic movements more easily and enjoyably. Therefore, the implementation of AR in physical movement learning, such as aerobic exercises, has proven to be effective as an innovative interactive learning aid.